Cancer and inflammation mechanisms : chemical, biological, and clinical aspects - Hiraku, Yūsuke; Kawanishi, Shōsuke, 1942-; Ōshima, Hiroshi, 1949- (Wiley, 2014)
A new perspective on the link between inflammation and cancer Inflammation is the human body's normal biological response to threats in the modern world, as well as a defense against the harmful influence of pathogens, the environment, and poor nutrition. But what happens when the inflammatory response is triggered repeatedly and sustained for long periods of time? Cancer and Inflammation Mechanisms: Chemical, Biological, and Clinical Aspects discusses the mechanisms by which chronic inflammation can lead to cancer, the various causative agents, and possible prevention methods. A compilation of the latest information coming out of the various fields of cancer research, this book provides a detailed look at inflammation-related carcinogenesis from the perspective of researchers at the forefront of the field. It takes an interdisciplinary approach to the topic, and provides comprehensive information about the major factors at work in inflammation, cancer, and the intersection of the two conditions. Topics include: A general overview of inflammation-related cancer The biochemistry of inflammation and its effects on DNA Molecular biology and the role of microRNA in carcinogenesis Specific causative agents including oncogenic viruses, asbestos, and nanomaterial Anti-inflammatories, nutraceuticals, and other preventative measures A deeper understanding of the mechanisms behind inflammation-related carcinogenesis can lead to better patient outcomes by improving diagnostics and prevention, as well as altering the approach to treatment. Cancer and Inflammation Mechanisms: Chemical, Biological, and Clinical Aspects provides the knowledge base researchers need to push the field forward.